1999
DOI: 10.4319/lo.1999.44.8.2017
|View full text |Cite
|
Sign up to set email alerts
|

Major flux of terrigenous dissolved organic matter through the Arctic Ocean

Abstract: High‐latitude rivers supply the Arctic Ocean with a disproportionately large share of global riverine discharge and terrigenous dissolved organic matter (DOM). We used the abundance of lignin, a macromolecule unique to vascular plants, and stable carbon isotope ratios (δ13C) to trace the high molecular weight fraction of terrigenous DOM in major water masses of the Arctic Ocean. Lignin oxidation products in ultrafiltered DOM (UDOM; >1,000 Da) from Arctic rivers were depleted in syringyl relative to vanillyl ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
277
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(298 citation statements)
references
References 30 publications
18
277
1
2
Order By: Relevance
“…Dissolved organic carbon studies in the Arctic Ocean and surrounding seas have concluded that despite the number of large rivers that supply the region, in situ production is the largest source of dissolved organic carbon (Wheeler et al 1997). Lignin tracer studies in Arctic water masses have shown that the dissolved organic carbon in the Greenland Sea gyre contains a low amount of lignin oxidation products and was enriched in 13 C (Opsahl et al 1999). From this it was deduced that terrestrial dissolved organic matter plays a relatively insignificant role in carbon cycling in the Greenland Sea.…”
Section: ϫ64a375mentioning
confidence: 99%
See 2 more Smart Citations
“…Dissolved organic carbon studies in the Arctic Ocean and surrounding seas have concluded that despite the number of large rivers that supply the region, in situ production is the largest source of dissolved organic carbon (Wheeler et al 1997). Lignin tracer studies in Arctic water masses have shown that the dissolved organic carbon in the Greenland Sea gyre contains a low amount of lignin oxidation products and was enriched in 13 C (Opsahl et al 1999). From this it was deduced that terrestrial dissolved organic matter plays a relatively insignificant role in carbon cycling in the Greenland Sea.…”
Section: ϫ64a375mentioning
confidence: 99%
“…This is one of the driving forces in the global thermohaline circulation, which has considerable control over Earth's climate (Broeker 1997) and the global carbon cycle. There is an ongoing debate about how much of the DOM pool has its origin from land and how much is produced autocthonously in the marine environment both in coastal areas and in the open oceans, like the Greenland Sea (Wheeler et al 1997;Opsahl et al 1999). The differentiation has previously been quantified by in-depth chemical analyses (e.g., Opsahl et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From a molecular perspective, terrigenous components can be traced in aquatic systems by lignin-derived phenols (Opsahl and Benner, 1997;Hernes and Benner, 2006) and pyrogenic black carbon, a product of biomass burning (Dittmar and Paeng, 2009;Jaffé et al, 2013). Mobilized from soils and subsequently transported to the oceans by rivers, terrigenous DOM contributes between o1% of the dissolved organic carbon (DOC) in the Pacific and up to 33% of the DOC in the Arctic Ocean (Opsahl and Benner, 1997;Opsahl et al, 1999;Hernes and Benner, 2002). The decomposition pathways of terrigenous DOM in the ocean are still not fully constrained.…”
Section: Introductionmentioning
confidence: 99%
“…The Arctic Ocean has the most extensive shelves of any ocean basin, covering about 50 % of its total area. Relative to other ocean basins, rivers play a disproportionately important role in the Arctic Ocean, which contains only about 1 % of the volume of the world's oceans yet receives approximately 10 % of the global terrigenous dissolved organic carbon (DOC) load (Aagaard et al, 1985;Opsahl et al, 1999). The DOC concentrations in coastal Arctic waters are twice higher than those in the Atlantic and Pacific oceans (Cauwet and Sidorov, 1996), highlighting the tight coupling of the Arctic Ocean with terrestrial catchments (Meon and Amon, 2004).…”
Section: Introductionmentioning
confidence: 99%